Elucidating causes of COVID-19 infection and related deaths after vaccination. Issue 5 (September 2021) - Jain, Vijay Kumar; Iyengar, Karthikeyan P.; Ish, Pranav
Abstract: Background and aims: Symptomatic or asymptomatic COVID-19 infection has been reported in vaccination. In the current article, we try to elucidate various causes behind COVID-19 infection and mortality following COVID-19 vaccination and suggest possible strategies to counteract this threat. Methods: We carried out a comprehensive review of the literature using suitable keywords such as 'COVID-19', 'Pandemics', 'Vaccines', 'Mortality', 'deaths', 'infections', and 'India' on the search engines of PubMed, SCOPUS, Google Scholar, and ResearchGate in from January to May 2021. Epidemiology, risk factors, Adverse Events Following Immunization (AEFI) and mortality after COVID-19 vaccination were assessed. Results: A number of factors have been associated with symptomatic or asymptomatic COVID-19 infection reported after vaccination. A high viral load, comorbidities, mutant strains, Variants of Concern (VOC) leading to Vaccine escape and casual attitude towards COVID Appropriate Behaviors appear to be the most important factors for infection and deaths after COVID-19 vaccination. Conclusions: COVID-19 Infection and mortality after COVID-19 vaccination are of great concern. Application of COVID Appropriate Behaviour (CAB) before and after vaccination is essential for the population. Effective Vaccines against mutant strains and enhanced vaccination drive are key strategies to avoid this quintessential threat. Early medical intervention in high-risk groups can prevent overall mortality. Highlights Box: Mortality due to COVID-19 infection even after full COVID-19 vaccination is being recognized. Reports suggest only a small proportion have COVID-19 infection following the two doses of vaccination. Sloppy attitude towards COVID Appropriate Behavior and false sense of security after vaccination should be avoided. Data Surveillance of hospitalized patients or who died due to COVID-19 after vaccination can elucidate exact reasons.